Teachers' Pedagogical Competence in Designing Deep Learning and HOTS Assessment in Elementary Schools: A Systematic Literature Review - Setiyowati, Endang; Puspita, Ari Metalin Ika; Mariana, Neni (Journal of Innovation and Research in Primary Education, 2025)
This systematic literature review examines teachers' pedagogical competence in designing deep learning and Higher-Order Thinking Skills (HOTS) assessment in elementary schools. The study analyzed 27 peer-reviewed articles published between 2020 and 2025, focusing on three primary dimensions: pedagogical competence in HOTS-based learning design, assessment development, and impact on student learning outcomes. The findings reveal that elementary school teachers demonstrate moderate to good pedagogical competence in designing HOTS-based learning, with strengths in lesson planning and implementation but challenges in assessment development and consistent application. Key factors influencing successful HOTS implementation include professional learning communities, continuous training programs, technology integration, and institutional readiness. The review identifies significant gaps in teachers' ability to develop creative and evaluative assessment instruments, with most teachers relying on analytical-level questions. Furthermore, the integration of HOTS assessment with deep learning approaches shows positive impacts on students' critical thinking skills and learning outcomes. The study recommends establishing systematic professional development programs, strengthening teacher learning communities, developing comprehensive HOTS assessment instruments, and fostering collaboration between stakeholders. This review contributes to understanding the current state of pedagogical competence in HOTS implementation and provides evidence-based recommendations for improving elementary education quality through enhanced teacher competence in deep learning and assessment practices.